2019
DOI: 10.1002/ecs2.2523
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying specialist avifaunal decline in grassland birds of the Northern Great Plains

Abstract: Habitat specialists are declining worldwide, often paralleling rapid loss of habitat. Grassland habitats across North America are declining precipitously, due in part to intense conversion of grasslands to agriculture and rangelands, and specialist communities reliant upon this landscape are at particular risk of decline and collapse. We explored the relationship between grassland habitat specialism in birds and species population trends using several different grassland specialism indices (GSIs). Our data sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 43 publications
(77 reference statements)
0
27
0
Order By: Relevance
“…This confluence (i.e., urban development at ecoregion junctions) may threaten vulnerable ecosystems and species, more specifically where SVs linked to agriculture, development, energy, and economy are highly valued (cf. Bernath‐Plaisted and Koper 2016, Correll et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This confluence (i.e., urban development at ecoregion junctions) may threaten vulnerable ecosystems and species, more specifically where SVs linked to agriculture, development, energy, and economy are highly valued (cf. Bernath‐Plaisted and Koper 2016, Correll et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in settlement patterns of grasshopper and Botteri's sparrows in response to invasions by two structurally different grasses demonstrates how habitat preferences and structural characteristics of novel plants interact to influence habitat use, and ultimately species' distributions. This can have important implications for the conservation of grassland specialists, as the degree of habitat specialism has been linked negatively to population trends (Correll et al 2019) and to increased vulnerability to environmental change (Clavel et al 2011, Correll et al 2016. 3).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that structural differences between nonnative plants and the native plants they displace can alter the quantity of habitat available to animals, especially species with narrow habitat breadths. This can have important implications for the conservation of grassland specialists, as the degree of habitat specialism has been linked negatively to population trends (Correll et al 2019) and to increased vulnerability to environmental change (Clavel et al 2011, Correll et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that Baird's Sparrows are simply more sensitive to environmental conditions than Grasshopper Sparrows as a consequence of inherent life history differences. Specialists species are highly successful when operating within ideal habitat conditions, but they have a limited ability adapt to sub-optimal or marginal environments (Correll et al 2019). For example, it is possible that Baird's sparrow was less successful at foraging in habitat that is partially degraded by non-native plant species than Grasshopper Sparrow, resulting in higher fledging mortality for Baird's sparrow.…”
Section: Species Differencesmentioning
confidence: 99%
“…The two species share similar habitat preferences and reproductive ecology in the NGP (Jones et al 2010, Lipsey andNaugle 2017) and both are shortdistance migrants that winter in the desert grasslands of the southwestern United States and Northern Mexico (Vickery 1996, Green et al 2002. However, despite apparent ecological similarities, the two species also present an interesting contrast with respect to degree of habitat specialism (Correll et al 2019); Baird's Sparrow is narrowly range-restricted to the NGP (however see Youngberg et al 2020) and highly specialized to mixed-grass prairie ecosystems during the breeding season (see Green et al 2002) while Grasshopper Sparrow is continently distributed and found in a greater variety of surrogate grasslands and opencountry habitats (Vickery 1996).…”
Section: Introductionmentioning
confidence: 99%